Notes on winter flies Trichoceridae (Diptera) of Mongolia with description of new species ANDRIUS PETRAŠIŪNAS & SIGITAS PODĖNAS (Lithuania) - Petrašiūnas, Andrius; Podėnas, Sigitas (Zootaxa, 2011)
The family of winter flies Trichoceridae is newly recorded for Mongolia. Four species, Trichocera (Metatrichocera) gigantea (Dahl), T. (M.) mackenziei (Dahl), T. (Saltrichocera) regelationis (Linnaeus) and T. (Trichocera) hiemalis (De Geer) are first recorded in Mongolia from sampling during 1996, 2003–2006, 2008. A new species, Trichocera (Saltrichocera) chuluuta, is described from specimens collected during the fieldwork of the Mongolian Aquatic Insect Survey Project in western and north-central Mongolia.